Determinan Profitabilitas Perbankan di BEI Tahun 2022-2024 - Isna Inayah; Arditya Dian Andika; Ira Septriana; Entot Suhartono (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the effect of the LDR, CAR, NIM, BOPO, and NPL ratios on banking profitability, as measured by Return on Assets (ROA). This study uses a quantitative approach with multiple linear regression analysis. The data used are secondary data in the form of financial statements of banking companies listed on the Indonesia Stock Exchange for the years 2022-2024. Purposive sampling resulted in 120 samples. The results show that LDR and NIM have a positive and significant effect on profitability, indicating that increased lending and net interest income can increase bank profits. BOPO has a negative and significant effect on profitability, indicating that operational efficiency is an important factor in improving financial performance. Meanwhile, CAR and NPL do not significantly affect profitability, indicating that capital adequacy and credit risk have not directly affected banks' ability to generate profits during the study period.